Recent advances in human cytomegalovirus: a comprehensive review of pathogenic mechanisms, virus-host interactions, and antiviral strategies - Xia, Ying; Zhang, Ji; Shui, Xiaochuan; Wang, Chao; Zhang, Shuaijie; Chai, Wenqi; Yang, Yang; Shen, Liang; Wang, Chunhua (Frontiers in Immunology, 2026)
Human cytomegalovirus (HCMV), recognized as the largest known DNA virus in the Herpesviridae family, is widely disseminated throughout the human population and poses a substantial threat to public health. HCMV is highly infectious. A majority of HCMV-infected individuals usually exhibit asymptomatic latent infections, while the immunocompromised or immunosuppressed populations infected with HCMV have high mortality. HCMV has long stood as a hot topic of research in the international virology community, and elucidating its pathogenic mechanisms is broadly regarded as a prerequisite for the development of vaccines and effective therapeutic drugs. This review presents a comprehensive and detailed analysis of the advances in the biological characteristics, pathogenesis, virus-host interactions, and the preventive and therapeutic strategies targeting HCMV infection. It will provide valuable insights and references for uncovering the pathogenic mechanisms of HCMV, identifying new drug targets, and developing potential immunotherapies.